Proceedings of the 2021 ACM SIGCOMM 2021 Conference 2021
DOI: 10.1145/3452296.3472928
|View full text |Cite
|
Sign up to set email alerts
|

Seven years in the life of Hypergiants' off-nets

Abstract: Content Hypergiants deliver the vast majority of Internet traffic to end users. In recent years, some have invested heavily in deploying services and servers inside end-user networks. With several dozen Hypergiants and thousands of servers deployed inside networks, these off-net (meaning outside the Hypergiant networks) deployments change the structure of the Internet. Previous efforts to study them have relied on proprietary data or specialized per-Hypergiant measurement techniques that neither scale nor gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…In terms of benefits, CDIs replicate and cache the content at multiple points-of-presence worldwide [40], often close to the edge and with direct peering agreements (between the CDI and the users' access networks), which pushes flattening of the Internet topology [11,31,43,72]. These deployments can result in lower page loading times for the end user due to shorter content delivery paths (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of benefits, CDIs replicate and cache the content at multiple points-of-presence worldwide [40], often close to the edge and with direct peering agreements (between the CDI and the users' access networks), which pushes flattening of the Internet topology [11,31,43,72]. These deployments can result in lower page loading times for the end user due to shorter content delivery paths (cf.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the use of these CDIs in the measurement data, we apply a methodology that considers (1) DNS redirection through CNAME records and (2) the content location based on the announcing AS. In this way, we also account for cases in which a CDI redirects the client to the closest content replica through a CNAME record, which can point to an ISP content cache for instance, and would therefore be mapped to the ASN of the ISP instead of that of the CDI [29,43,77]. If a CNAME record matches a regular expression, the second step, which applies ASN-based identification is not applied.…”
Section: Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…They are typically deployed by entities other than ISPs and provide a means for service differentiations that do not violate network neutrality regulations (Stocker et al, 2017(Stocker et al, , 2020. The majority of Internet traffic is already delivered via third-party CDNs like Akamai or Cloudflare or the distributed serving infrastructures of large CPs like Google, Netflix or Facebook that have strongly expanded their footprints of servers deployed within ISP networks in recent years (Gigis et al, 2021;Labovitz, 2019Labovitz, , 2020. 12 In addition to these developments, the emergence of 5G and beyond mobile broadband access networks emphasizes the future role of applications and use cases that vary considerably in their networking demands.…”
Section: Table 3 (Continued)mentioning
confidence: 99%
“…Previous studies [3], [4] demonstrated that DPI improved the accuracy. However, many recent communication flows are encrypted [5] with the transport layer security (TLS) protocol. Identification methods cannot analyze almost all the packet payloads that are encrypted by TLS.…”
Section: Introductionmentioning
confidence: 99%